PKM DESA GITIK DALAM PENINGKATAN PRODUKSI INDUSTRI RUMAH TANGGA TAHU - Shinta Setiadevi; Dian Ridlo Pamuji (ELEMEN : JURNAL TEKNIK MESIN, 2018)
Soybean is one of the Banyuwangi district food crops which has the potential to continue to be seeded besides rice, corn, peanuts, green beans, cassava, and sweet potatoes. Banyuwangi Regency was designated as one of the national soybean barns by the Ministry of Agriculture of the Republic of Indonesia since 2015 with an area of 100 hectares in Muncar District. The soybean varieties developed are New Superior Varieties (VUB). The productivity obtained eaches 3 tons per hectare beyond the national soybean productivity average if 1.5 tons per hectare. The most important part of soybeans is soybean seeds. One product produced by soybean seeds is tofu. Tofu is a staple food for the people of Indonesia, causing demand to continue to increase so IKM knows that it continues to strive to meet market needs. Banyuwangi Regency makes processed tofu as a typical snack called tahu walik. Tahu walik is one of the typical Banyuwangi snacks made from fried tofu which is reserved so that inside of the tofu is outside and filled with chicken dough. The majority of the people in Gitik Village, Rogojampi District have a business processing soybeans into white tofu products and household-scale fried tofu. The quality of the tofu produced still has high water content. The amount of tofu produced is still small, this is caused by the use of traditional tofu presses. The transition from traditional tofu presses to modern ones is expected to be able to improve the quality and quantity of products obtained.